Stress Analysis of Occlusal Forces in Canine Teeth and Their Role in the Development of Non-Carious Cervical Lesions: Abfraction - Shihab A. Romeed; Raheel Malik; Stephen M. Dunne (Hindawi Limited, 2012)
Non-carious cervical tooth lesions for many decades were attributed to the effects of abrasion and erosion mainly through toothbrush trauma, abrasive toothpaste, and erosive acids. However, though the above may be involved, more recently a biomechanical theory for the formation of these lesions has arisen, and the term abfraction was coined. The aim of this study was to investigate the biomechanics of abfraction lesions in upper canine teeth under axial and lateral loading conditions using a three-dimensional finite element analysis. An extracted human upper canine tooth was scanned by μCT machine (Skyscan, Belgium). These μCT scans were segmented, reconstructed, and meshed using ScanIP (Simpleware, Exeter, UK) to create a three-dimensional finite element model. A 100 N load was applied axially at the incisal edge and laterally at 45° midpalatally to the long axis of the canine tooth. Separately, 200 N axial and non-axial loads were applied simultaneously to the tooth. It was found that stresses were concentrated at the CEJ in all scenarios. Lateral loading produced maximum stresses greater than axial loading, and pulp tissues, however, experienced minimum levels of stresses. This study has contributed towards the understanding of the aetiology of non-carious cervical lesions which is a key in their clinical management.